Evaluation of Stability between Conventional Femoral Stem and Short Stem in Total Hip Arthroplasty - Muhammad Syahrul Ashraff Said; Abdullah, Haslina (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Abstract Total Hip Arthroplasty (THA) is a surgical procedure that involves replacing a damaged or diseased hip joint with an artificial implant. This study focused on the design aspect of the femoral stem to enhance implant stability, a critical factor in the success of THA. The primary objectives of this research are threefold: firstly, to design different types of design using Solidwork. Next, to perform a simulation of stability analysis using Abaqus software; and thirdly, to evaluate on the assessment of stability at the bone-implant interface. The analysis in Abaqus software involves a comprehensive simulation of the mechanical behavior of the femoral stem under normal walking conditions. In this study, the factors such as material properties, load distribution, and contact mechanics at the bone-implant interface has been evaluated. Finite element analysis (FEA) has been implements to exam the displacement of the implant. The simulation results show that the conventional stem provides more stability, while the shorter stem provides less stability, with the collarless option positioned between the conventional and short stem. This shows that the stem design has a significant impact on the stability of the bone-implant interface. The study emphasizes that the stability of the bone-implant interface is a key determinant in the success of THA. In summary, the various designs of femoral stems significantly affect the stability of the implant. This study emphasizes the vital importance of femoral stem design in shaping and impacting the overall stability of the bone implant